Combinatorial Effect of Abiraterone Acetate and NVP-BEZ235 on Prostate Tumor Progression in Rats - Gonçalves, Bianca Facchim [UNESP]; de Campos, Silvana Gisele Pegorin [UNESP]; Fávaro, Wagner José; Brandt, Joyce Zalotti [UNESP]; Pinho, Cristiane Figueiredo [UNESP]; Justulin, Luis Antônio [UNESP]; Taboga, Sebastião Roberto [UNESP]; Scarano, Wellerson Rodrigo [UNESP] (Springer Nature, 2018)
Use of drug combinations that target different pathways involved in the development and progression of prostate cancer (PCa) has emerged as an alternative to overcome the resistance caused by drug monotherapies. The antiandrogen abiraterone acetate and the PI3K/Akt inhibitor NVP-BEZ235 (BEZ235) may be suitable options for the prevention of drug resistance and the inhibition of PCa progression. The aim of the present study was to evaluate whether abiraterone acetate and BEZ235 achieve superior therapeutic effects to either drug administered as monotherapy, in the early stages of PCa in an androgen-dependent system. Our study showed that each drug might impair tumor growth by reducing proliferation and increasing cell death when administered as monotherapy. However, tumor growth continued to progress with each drug monotherapy and some important side effects were related to BEZ. Conversely, when used in combination, the drugs impaired the inflammatory response, decreased hyperplastic lesions, and blocked tumor progression from premalignant to a malignant stage. Our data showed that the strategy to block the androgenic and PI3K/AKT/mTOR pathway is an effective therapeutic option and should be investigated including distinct PI3K pathway inhibitors.